Bis(arylimino)pyridyl cobalt catalysts for copolymerization of buta-1, 3-diene with ethene. (26th June 2019) - Železník, Ondřej; Merna, Jan
Abstract: A series of cobalt (II), iron (II) and iron (III) bis(arylimino)pyridyl complexes [2, 6-(ArN=CMe)2 C5 H3 N]CoCl2, where Ar is 2, 4, 6-Me3 C6 H2; 2, 6-Me2 C6 H3; 2, 6- i Pr2 C6 H3 and 2- t BuC6 H4, ; [2, 6-(ArN=CCl)2 C5 H3 N]CoCl2, where Ar is 2, 4, 6-Me3 C6 H2 and 2, 6-iPr2 C6 H3, and [2, 6-(ArN=CMe)2 C5 H3 N]FeCl2, where Ar is 2, 4, 6-Me3 C6 H2 ; [2, 6-(ArN=CMe)2 C5 H3 N]FeCl3, where Ar is 2, 4, 6-Me3 C6 H2 was prepared and, after activation with an alkylaluminium cocatalysts (Al2 Et3 Cl3 or methylaluminoxane), investigated for ethene and butadiene homopolymerization and their copolymerization. Only the cobalt complexes resulted in the effective creation of butadiene-ethene copolymers. According to the cocatalyst preference, two sets of butadiene-ethene copolymers were prepared. Ethene rich (60–85%) crystalline copolymers were obtained using methylaluminoxane and butadiene rich (70–90%) amorphous copolymers using Al2 Et3 Cl3 . Mechanism of cobalt complexes activation was investigated in-situ by UV-VIS spectroscopy. To our best knowledge, this is the first time that bis(arylimino)pyridyl cobalt complexes have been shown to copolymerize butadiene with ethene. The copolymerization activated by Al2 Et3 Cl3 is cis -1, 4-selective and provides elastomeric material. Graphical abstract: Image 1 Highlights: Ethene and butadiene copolymerize by bis(arylimino)pyridyl Co complexes. Activation by MMAO results in structurally heterogeneous ethene rich copolymers. Activation by Al2 Et3 Cl3 gives amorphous cis -1, 4-butadiene rich rubbery copolymers. Amorphous copolymers have multi- block structure with non-crystallizing PE segments. Catalyst activation mechanism was investigated by UV–vis spectroscopy.